SmartVisio: Interactive Sketch Recognition with Natural Correction and Editing - Wu, Jie; Wang, Changhu; Zhang, Liqing; Rui, Yong (ACM Conference on Multimedia, 2014)
In this work, we introduce the SmartVisio system for in- teractive hand-drawn shape/diagram recognition. Di er- ent from existing work, SmartVisio is a real-time sketch recognition system based on Visio, to recognize hand-drawn owchart/diagram with exible interactions. This system enables a user to draw shapes or diagrams on the Visio in- terface, and then the hand-drawn shapes are automatically converted to formal shapes in real-time. To satisfy the inter- action needs from common users, we propose an algorithm to detect a user's correction and editing during drawing, and then recognize in real time. We also propose a novel symbol recognition algorithm to better recognize or di er- entiate some visually similar shapes. By enabling users' nat- ural correction/editing on various shapes, our system makes owchart/diagram production much more natural and eas- ier.